2007
DOI: 10.1634/stemcells.2007-0049
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Activates Side Population Cells in Kidney and Partially Reverses Chronic Renal Injury

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
4
43
1
1
Order By: Relevance
“…If SP cells exist in patients with renal failure, it may be possible to reverse the function by activating the cells, in situ, as in the case of the animal model. 6 Taken together, our results for the first time confirm the existence of SP cells, adult stem-like cells, in the human kidney, and suggest that the cells could be good targets for clinical regenerative medicine.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…If SP cells exist in patients with renal failure, it may be possible to reverse the function by activating the cells, in situ, as in the case of the animal model. 6 Taken together, our results for the first time confirm the existence of SP cells, adult stem-like cells, in the human kidney, and suggest that the cells could be good targets for clinical regenerative medicine.…”
Section: Resultssupporting
confidence: 74%
“…3 Several groups have published reports regarding SP cells in the kidney. [3][4][5][6] Hishikawa and colleagues 4 reported that the SP cells isolated from the kidney of acute renal failure express high levels of renoprotective factors, such as hepatocyte growth factor, vascular endothelial growth factor, leukemia inhibitory factor and infusion of the renal SP cells improves renal function. The recent reports support the notion that the beneficial effects of tissue regeneration seem to be endocrine in nature.…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…All groups agree that, as for MSCs, SP cells shown multipotentiality and elicit an improvement in renal function via a humoral role, rather than by directly contributing to the replacement of renal tissue [73,74,76]. How this occurs is not clear, but the expression of renoprotective factors such as BMP7 has been reported to be higher in the SP than the non-SP fraction of the kidney [77].…”
Section: Progenitors Isolated Based Upon Cellular Behaviourmentioning
confidence: 80%
“…3 Interestingly, very recent studies also reported that treatment with HDAC inhibitors reduces epithelial-to-mesenchymal transition 15 and fibrosis in obstructive nephropathy, 16 regulates bone morphogenic protein 7 in the regenerative response to ischemia, 17 and prevents the progression of accelerated nephrotoxic serum nephritis toward glomerulosclerosis. 18 The central role of stem or progenitor cells in maintaining the integrity and functionality of organ tissues also suggests their manipulation might engender adverse effects. 12 Indeed, zebrafish larvae treated with HDAC inhibitors develop edema, 10 which suggests that deregulated expansion of renal progenitor cells can disrupt organ regeneration or function.…”
Section: From Proteus To Prometheusmentioning
confidence: 99%